Characterization techniques for heterogeneous nucleation from the gas phase. (January 2022) - Winkler, Paul M.; Wagner, Paul E.
Abstract: Heterogeneous nucleation constitutes the initial step in the formation of new aerosol particles that evolve on the surface of pre-existing (seed) particles. To this end the interaction of vapor and seed particle plays a critical role which is governed by the seed particle's size, composition, solubility, electrical charge state as well as the chemical nature of the vapor and the wetting properties of the condensing liquid with the underlying surface. Despite being a process on the nanoscale under most conditions of relevance the effect of heterogeneous nucleation has global implications via the formation of clouds, and is technically utilized in condensation particle counters for the detection of nanoparticles. Proper techniques for the characterization of heterogeneous nucleation thus serve a better fundamental understanding and improve the detectability of nanoparticles. Here we review state-of-the-art experimental and theoretical techniques allowing quantitative analysis of heterogeneous nucleation and providing insight to properties of nucleating clusters. Building upon current knowledge we identify and discuss open questions in the field motivating prospective future research. Highlights: Observation of heterogeneous nucleation on seed particles with diameters well below Kelvin diameter. Proving the validity of the Kelvin equation on nearly molecular scale. Characterization of cluster geometry from combined application of Kelvin equation and the heterogeneous nucleation theorem. Experimental determination of microscopic contact angle and line tension. Research needs in heterogeneous nucleation.